Carbon storage and energy production of Eucalyptus urophylla developed in dryland ecosystems at East Nusa Tenggara - Ronggo Sadono; Wahyu Wardhana; Fahmi Idris; Pandu Yudha Adi Putra Wirabuana (Journal of Degraded and Mining Lands Management, 2021)
The development of Eucalyptus urophylla in dryland ecosystems plays an important contribution to support climate change mitigation and renewable energy diversification. However, the information about the potential of E. urophylla for carbon reduction and energy production is rarely documented, even though it is necessary as fundamental considerations to determine the best strategy for sustainable natural resources management, primarily in dryland ecosystems. This study aimed to quantify the carbon storage and energy production of E. urophylla established in dryland ecosystems at East Nusa Tenggara. The study site is located in a eucalyptus plantation managed by Timor Tengah Selatan Forest Management Unit. Destructive sampling was conducted on 25 sample trees that were evenly distributed from small to big ones. The percentage of carbon content in every tree component, namely stem, branch, and foliage, was determined using elemental analysis, while the calorific value of each tree component was analyzed using a bomb calorimeter. Carbon storage in each component was calculated by multiplying biomass and the percentage of carbon content, while the energy production was computed by multiplying high heating value and biomass from every tree component. The results found the mean carbon storage of E. urophylla in the study site was 55.51 kg tree-1 with a minimum of 6.34 kg tree-1 and a maximum of 184.76 kg tree-1. The percentage of carbon content in the foliage was lower than other tree components by approximately 34.1%. Interestingly, the calorific value of foliage was relatively higher than stem and branch with around 5,252 kcal kg-1. The energy production of E. urophylla ranged from 252.6 to 7,813.3 MJ tree-1 with an average of 2,357.87 MJ tree-1. According to the results, this study concluded the development of E. urophylla in dryland ecosystems demonstrated a meaningful contribution to carbon absorption and energy production at East Nusa Tenggara.